Single Tree Vegetation Depth Estimation Tool for Satellite Services Link Design - Hasirci, Zeynep; Cavdar, I. Hakki; Ozturk, Mehmet (Společnost pro radioelektronické inženýrství, 2016)
Attenuation caused by tree shadowing is an important factor for describing the propagation channel of satellite services. Thus, vegetation effects should be determined by experimental studies or empirical formulations. In this study, tree types in the Black Sea Region of Turkey are classified based on their geometrical shapes into four groups such as conic, ellipsoid, spherical and hemispherical. The variations of the vegetation depth according to different tree shapes are calculated with ray tracing method. It is showed that different geometrical shapes have different vegetation depths even if they have same foliage volume for different elevation angles. The proposed method is validated with the related literature in terms of average single tree attenuation. On the other hand, due to decrease system requirements (speed, memory usage etc.) of ray tracing method, an artificial neural network is proposed as an alternative. A graphical user interface is created for the above processes in MATLAB environment named vegetation depth estimation tool (VdET).
Keywords: MATLAB estimation tool; ray tracing; satellite services; tree attenuation; tree shape; vegetation depth.